Pembuktian Kasus Hukum Perkawinan - Yuni Priskila Ginting; Putu Davis Justin Thenata; Ryan Jovan Susanto; Jeanette Olivia Kurniawati; Jessica Carol Lee (Jurnal Syntax Admiration, 2024)
This study discusses the issue of marriage according to civil law in Indonesia, especially related to the importance of marriage registration to ensure the validity of marriage and the legal impact arising from unregistered marriages. This study aims to identify relevant legal provisions in marriage cases, especially those related to unregistered marriages, otherwise known as sirri marriages. The method used in this study is normative juridical, with secondary data from literature studies. The results of the study show that unregistered marriages have the potential to cause various legal problems, both for married couples and children born from the marriage. The conclusion of this study emphasizes the importance of marriage registration as formal and legal evidence that protects the civil rights of husband and wife and children born from a valid marriage.